2017
DOI: 10.1042/bsr20170767
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin alleviates inflammation and muscle weakness, while altering the Treg/Th17 balance in a rat model of myasthenia gravis

Abstract: Myasthenia gravis (MG) is an autoimmune disease commonly treated with immunosuppressants. We evaluated the novel immunosuppressant, rapamycin (RAPA), in a rat model of experimental autoimmune MG (EAMG). Mortality rates in the RAPA (12%) were significantly down compared with the EAMG (88%) or cyclophosphamide (CTX) (68%) intervention groups. Muscular weakness decreased after both RAPA and CTX treatment. However, Lennon scores were lower (1.74 ± 0.49, 3.39 ± 0.21, and 3.81 ± 0.22 in RAPA, CTX, and EAMG groups, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…Imbalances in helper T cells and T reg lymphocytes induce MG [ 26 ]. In this study we observed an increased proportion of T h 1, T h 2, and T h 17 lymphocytes in EAMG and decreased T reg lymphocyte numbers, in agreement with previous reports [ 3 ]. Dysregulated numbers of CD4 + helper T cells have been linked to a loss of immune balance [ 26 , 27 ] as reported in multiple sclerosis, systemic lupus erythematosus, and MG [ 26 28 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Imbalances in helper T cells and T reg lymphocytes induce MG [ 26 ]. In this study we observed an increased proportion of T h 1, T h 2, and T h 17 lymphocytes in EAMG and decreased T reg lymphocyte numbers, in agreement with previous reports [ 3 ]. Dysregulated numbers of CD4 + helper T cells have been linked to a loss of immune balance [ 26 , 27 ] as reported in multiple sclerosis, systemic lupus erythematosus, and MG [ 26 28 ].…”
Section: Discussionsupporting
confidence: 93%
“…Despite extensive research in the field, the exact pathogenesis of MG remains unclear [ 2 ]. MG leads to cellular immune abnormalities mediated by CD4 + T lymphocytes [ 3 ]. Native CD4 + helper T lymphocytes (T h 1, T h 2, and T h 17 subsets) [ 4 ] are elevated in MG [ 5 ] and are correlated with higher AChR antibody titers [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anti-IL-6 monoclonal antibody has been reported to show good efficacy in patients with EAMG. Additionally, other studies have shown that rapamycin and artemisinin lessen motor symptoms in EAMG rats, with an ability of correcting Treg/Th17 imbalances ( 51 , 52 ). Rapamycin is the most common inhibitor targeting mTOR, which inhibits the differentiation of Th17 cells ( 53 ) and induces the proliferation of Treg cells ( 54 ) by inhibiting the mTOR signaling pathway.…”
Section: Significance Of Th17/treg Imbalances In Mg Progressionmentioning
confidence: 99%
“…Similarly, Rapa significantly improved symptoms in MG animal model rats (42). The mortality of rats after Rapa treatment was lower than that in rats administered the traditional immunosuppressant cyclophosphamide.…”
Section: Discussionmentioning
confidence: 76%